Cancer-Associated Fibroblasts in Gastric Cancer Regulate Macrophage Polarization through RCN3 Pathway - Lu Yang; Chang Zhou; Xin Zheng; Wei Zhang (Frontiers in Bioscience-Landmark, 2024)
Objective: To explore the role and molecular mechanism of cancer-associated fibroblasts (CAFs) in the tumor microenvironment of gastric cancer (GC). Methods: The expression of CAFs in GC patients was first assessed for abundance, and survival analysis was performed. Subsequently, The Cancer Genome Atlas (TCGA) data were used for differential analysis, survival analysis, and EPIC analysis, while single-cell data (GSE183904) were downloaded for differential analysis of CAFs. Clinical data pooling, univariate and multivariate Cox analysis, and immunofluorescence were carried out on clinical GC tissue samples to explore RCN3 expression within patient CAFs. Western blot and quantitative polymerase chain reaction (qPCR) were used to detect the expression of RCN3. The relationship between RCN3, PCSK6, and STAT1 was explored by chromatin immunoprecipitation (CHIP) experiments, and the effects of the genes on macrophage polarization were detected by detecting biomarkers of biological M1/M2. Results: CAFs in GC were found to be significantly higher compared to the normal group. Revealing the results of TCGA differential analysis, it was observed that GC exhibited a substantial upregulation in the expression levels of RCN3. The clinical statistics indicate a positive correlation between an elevated level of RCN3 expression and the T-stage classification of tumor size. In addition, RCN3 was found to have a significant impact on the overall survival of patients with gastric cancer, acting as an independent prognostic indicator. Analysis of single-cell data showed high expression of PCSK6 in macrophages, and immunofluorescence staining of samples from GC patients showed increased expression of PCSK6 on the cell membranes of macrophages in GC tissues. The subsequent cellular experiments confirmed RCN3 protein can regulate the expression of PCSK6, and PCSK6 regulates macrophage polarization through STAT1. Conclusions: CAFs regulate macrophage polarization through the RCN3/PCSK6/STAT1 pathway in GC.